INITIAL RESPONSES OF CARBONATE-RICH SHELF SEDIMENTS TO RISING ATMOSPHERIC PCO2 AND "OCEAN ACIDIFICATION": ROLE OF HIGH MG-CALCITES - Morse J.W.; Andersson A.J.; Mackenzie F.T. (My University, 2006)
Carbonate-rich sediments at shoal to shelf depths (<200 m) represent a major CaCO3 reservoir that can rapidly react to the decreasing saturation state of seawater with respect to carbonate minerals, produced by the increasing partial pressure of atmospheric carbon dioxide (pCO2) and "acidification" of ocean waters. Aragonite is usually the most abundant carbonate mineral in these sediments. However, the second most abundant (typically ?24 wt%) carbonate mineral is high Mg-calcite (Mg-calcite) whose solubility can exceed that of aragonite making it the "first responder" to the decreasing saturation state of seawater. For the naturally occurring biogenic Mg-calcites, dissolution experiments have been used to predict their "stoichiometric solubilities" as a function of mol% MgCO3. The only valid relationship that one can provisionally use for the metastable stabilities for Mg-calcite based on composition is that for the synthetically produced phases where metastable equilibrium has been achieved from both under- and over-saturation. Biogenic Mg-calcites exhibit a large offset in solubility from that of abiotic Mg-calcite and can also exhibit a wide range of solubilities for biogenic Mg-calcites of similar Mg content. This indicates that factors other than the Mg content can influence the solubility of these mineral phases. Thus, it is necessary to turn to observations of natural sediments where changes in the saturation state of surrounding waters occur in order to determine their likely responses to the changing saturation state in upper oceanic waters brought on by increasing pCO2. In the present study, we investigate the responses of Mg-calcites to rising pCO2 and "ocean acidification" by means of a simple numerical model based on the experimental range of biogenic Mg-calcite solubilities as a function of Mg content in order to bracket the behavior of the most abundant Mg-calcite phases in the natural environment. In addition, observational data from Bermuda and the Great Bahama Bank are also presented in order to project future responses of these minerals. The numerical simulations suggest that Mg-calcite minerals will respond to rising pCO2 by sequential dissolution according to mineral stability, progressively leading to removal of the more soluble phases until the least soluble phases remain. These results are confirmed by laboratory experiments and observations from Bermuda. As a consequence of continuous increases in atmospheric CO2 from burning of fossil fuels, the average composition of contemporary carbonate sediments could change, i.e., the average Mg content in the sediments may slowly decrease. Furthermore, evidence from the Great Bahama Bank indicates that the amount of abiotic carbonate production is likely to decline as pCO2 continues to rise. ? 2006 Elsevier Inc. All rights reserved.
Keywords: ACIDIFICATION; BIOGENIC DEPOSIT; CALCIUM CARBONATE; CARBON DIOXIDE; CHEMICAL OCEANOGRAPHY; SATURATION; SHELF SEDIMENT; SOLUBILITY; BERMUDA; GREAT BAHAMA BANK